Combined Carbon and Albedo Climate Forcing From Pine and Switchgrass Grown for Bioenergy - Ahlswede, Benjamin J.; O'Halloran, Thomas L.; Thomas, R. Quinn (Frontiers in Forests and Global Change, 2022)
Expanding and restoring forests decreases atmospheric carbon dioxide, a natural solution for helping mitigate climate change. However, forests also have relatively low albedo compared to grass and croplands, which increases the amount of solar energy they absorb into the climate system. An alternative natural climate solution is to replace fossil fuels with bioenergy. Bioenergy crops such as switchgrass have higher albedo than forest ecosystems but absorb less total carbon over their lifetime. To evaluate trade-offs in the mitigation potential by pine and switchgrass ecosystems, we used eddy covariance net ecosystem exchange and albedo observations collected from planted pine forests and switchgrass fields in eastern North America and Canada to compare the net radiative forcing of these two ecosystems over the length of typical pine rotation (30 years). We found that pine had a net positive radiative forcing (warming) of 5.4$±$2.8 $W m^{-2}$ when albedo and carbon were combined together (30 year mean). However the assumptions regarding the fate of harvested carbon had an important effect on the net radiative forcing. When we assumed all switchgrass carbon was emitted to the atmosphere while the harvested pine carbon was prevented from entering the atmosphere, the 30-year mean net radiative forcing reversed direction (-3.6$±$2.8 $W m^{-2}$). Overall, while the pine ecosystem absorbed more carbon than the switchgrass, the difference in albedo was large enough to result in similar climate mitigation potential at the 30-year horizon between the two systems, whereby the direction and magnitude of radiative forcing depends on the fate of harvested carbon.